Use of Peripheral Venous Blood Gas Analysis and Oximetry to Assess Respiratory Failure in the Emergency Department: Plinska analiza periferne venske krvi in pulzna oksimetrija za oceno akutne dihalne odpovedi v urgentni ambulanti - Golub, Jerneja; Gorenjak, Mario; Žuran Pilinger, Eva; Lešnik, Amadeus; Markota, Andrej (Acta Medico-Biotechnica, 2021)
Purpose: The diagnosis of acute respiratory failure (ARF) is based on arterial blood gas analysis (ABGA), which is associated with patient discomfort and requires an additional vascular puncture. Our aim was to compare ABGA with peripheral venous blood gas analysis (PVBGA) and pulse oximetry in adult patients with dyspnea and/or suspected ARF.Methods: We included 102 patients (56 males) in a prospective study performed in a medical emergency department from March–May 2019. Patients with overt signs of circulatory shock or severe respiratory failure were not included.Results: We showed significant positive correlations between ABGA and PVBGA results (for pH, ρ=0.590; for HCO3, ρ=0.901; and for pCO2, ρ=0.740), and insignificant differences between oxygen saturation based on ABGA and pulse oximetry (95% vs. 94%; p=0.49). When we subtracted 1 kPa from the venous pCO2 and added 4 kPa to the venous pO2 , there were no statistically significant differences between peripheral venous and arterial pCO2 and pO2 (4.8 vs. 4.7 kPa, p=0.26 and 9.5 vs. 8.9 kPa, p=0.21, respectively).Conclusion: The combination of PVBGA and pulse oximetry provided sufficient data to make clinical decisions in a select group of patients with dyspnea and/or ARF.
Keywords: acute respiratory failure; dyspnea; arterial blood gas analysis; hypercapnia; pulse oximetry